Eternals [videorecording (DVD)] - Zhao, Chloé; Burleigh, Patrick; Firpo, Ryan; Firpo, Kaz (Matthew Kazuo); Chan, Gemma, 1982-; Madden, Richard, 1986-; Nanjiani, Kumail; McHugh, Lia; Henry, Brian Tyree; Ridloff, Lauren, 1978-; Keoghan, Barry, 1992-; Ma, Tong-sŏk, 1971-; et al. (Marvel, 2022)
After the population is restored following Thanos' click, an unexpected tragedy forces a group of ancient aliens who have been living on Earth in secret for thousands of years out of the shadows to reunite against mankind's most ancient enemy, the Deviants.